Investigating associations between intestinal alterations and parasite load according to Bifidobacterium spp. and Lactobacillus spp. abundance in the gut microbiota of hamsters infected by Leishmania infantum - Fabine Correia Passos; Marcelo Biondaro Gois; Adenilma Duranes Sousa; Ananda Isis Lima de Marinho; Laura Corvo; Manoel Soto; Manoel Barral-Netto; Aldina Barral; Gyselle Chrystina Baccan (Memorias do Instituto Oswaldo Cruz, 2020)
BACKGROUND Visceral leishmaniasis (VL) is a tropical neglected disease with high associated rates of mortality. Several studies have highlighted the importance of the intestinal tract (IT) and gut microbiota (GM) in the host immunological defense. Data in the literature on parasite life cycle and host immune defense against VL are scarce regarding the effects of infection on the IT and GM. OBJECTIVES This study aimed to investigate changes observed in the colon of Leishmania infantum-infected hamsters, including alterations in the enteric nervous system (ENS) and GM (specifically, levels of bifidobacteria and lactobacilli). METHODS Male hamsters were inoculated with L. infantum and euthanised at four or eight months post-infection. Intestines were processed for histological analysis and GM analysis. Quantitative polymerase chain reaction (qPCR) was performed to quantify each group of bacteria: Bifidobacterium spp. (Bf) and Lactobacillus spp (LacB). FINDINGS Infected hamsters showed histoarchitectural loss in the colon wall, with increased thickness in the submucosa and the mucosa layer, as well as greater numbers of intraepithelial lymphocytes. Forms suggestive of amastigotes were seen inside mononuclear cells. L. infantum infection induced changes in ENS, as evidenced by increases in the area of colonic enteric ganglia. Despite the absence of changes in the levels of Bf and LacB during the course of infection, the relative abundance of these bacteria was associated with parasite load and histological alterations. MAIN CONCLUSIONS Our results indicate that L. infantum infection leads to important changes in the colon and suggest that bacteria in the GM play a protective role.